Investigations of the prevalence and virulence of Candida albicans in periodontal and endodontic lesions in diabetic and normoglycemic patients - Cinthya Cristina GOMES; Ludmila Silva GUIMARÃES; Larissa Christina Costa PINTO; Gabriela Alessandra da Cruz Galhardo CAMARGO; Maria Isabel Bastos VALENTE; Maria Inêz de Moura SARQUIS
Abstract Pulpal and periodontal tissues have similar microbiota that allows cross-contamination between the pulp and periodontal tissues. Objective The aim of this study was to investigate the prevalence of isolated Candida albicans from periodontal endodontic lesions in diabetic and normoglycemic patients, and the fungi's virulence in different atmospheric conditions. Material and Methods A case-control study was conducted on 15 patients with type 2 diabetes mellitus (G1) and 15 non-diabetics (G2) with periodontal endodontic lesions. Samples of root canals and periodontal pockets were plated on CHROMagar for later identification by polymerase chain reaction (PCR) and virulence test. Results C. albicans was identified in 79.2% and 20.8% of the 60 samples collected from diabetic and normoglycemic patients, respectively. Of the 30 samples collected from periodontal pockets, 13 showed a positive culture for C. albicans, with 77% belonging to G1 and 23% to G2. Of the 11 positive samples from root canals, 82% were from G1 and 18% from G2. Production of proteinase presented a precipitation zone Pz<0.63 of 100% in G1 and 72% in G2, in redox and negative (Pz=1), under anaerobic conditions in both groups. Hydrophobicity of the strains from G1 indicated 16.4% with low, 19.3% with moderate, and 64.3% with high hydrophobicity in redox. In G2, 42.2% had low, 39.8% had moderate, 18% had high hydrophobicity in redox. In anaerobic conditions, G1 showed 15.2% with low, 12.8% with moderate, and 72% with high hydrophobicity; in G2, 33.6% had low, 28.8% had moderate, and 37.6% had high hydrophobicity. There was statistical difference in the number of positive cultures between G1 and G2 (p<0.05) with predominance in G1. There was statistical difference for all virulence factors, except hemolysis (p=0.001). Conclusions Candida albicans was isolated more frequently and had higher virulence in diabetic patients.